Experience of a novel lung transplant program in Mexico - Zavala-Gómez, Mariana N.; Rodríguez-de la Garza, Patricia; Chavarria-Martinez, Uriel; Wong-Jaen, Manuel; Camacho-Ortiz, Adrián; Rizo-Topete, Lilia M.; López-Romo, Alicia E.; Fuentes-Puga, Vicente; Sánchez-Salazar, Sergio S. (Frontiers in Transplantation, 2024)
Lung transplantation stands as the gold standard therapy for patients in the end-stages of pulmonary disease. However, in numerous countries, candidates for lung transplant often die on the waiting list due to a shortage of donors and limited access to transplant centers. This article will delve into our hospital, Christus Muguerza's in Monterrey, Mexico, experience as the sole active lung transplant program in the country, having conducted 35 transplants from August 2017 to March 2023. We discuss the actual situation of lung transplantation in Mexico and the challenges we have faced over time, such as late patient referrals for evaluation and eventual transplantation. Additionally, we outline the challenges we anticipate as more transplant programs emerge in the country.